Effects of ionizing radiation on DNA methylation: from experimental biology to clinical applications. (4th May 2017) - Miousse, Isabelle R.; Kutanzi, Kristy R.; Koturbash, Igor
Abstract: Purpose: Ionizing radiation (IR) is a ubiquitous environmental stressor with genotoxic and epigenotoxic capabilities. Terrestrial IR, predominantly a low-linear energy transfer (LET) radiation, is being widely utilized in medicine, as well as in multiple industrial applications. Additionally, an interest in understanding the effects of high-LET irradiation is emerging due to the potential of exposure during space missions and the growing utilization of high-LET radiation in medicine. Conclusions: In this review, we summarize the current knowledge of the effects of IR on DNA methylation, a key epigenetic mechanism regulating the expression of genetic information. We discuss global, repetitive elements and gene-specific DNA methylation in light of exposure to high and low doses of high- or low-LET IR, fractionated IR exposure, and bystander effects. Finally, we describe the mechanisms of IR-induced alterations to DNA methylation and discuss ways in which that understanding can be applied clinically, including utilization of DNA methylation as a predictor of response to radiotherapy and in the manipulation of DNA methylation patterns for tumor radiosensitization.